Pharmacokinetic modelling of orally administered cannabidiol and implications for medication control in horses - Eichler, Fabienne; Poźniak, Błażej; Machnik, Marc; Schenk, Ina; Wingender, Anke; Baudisch, Natalie; Thevis, Mario; Bäumer, Wolfgang; Lischer, Christoph; Ehrle, Anna (Frontiers in Veterinary Science, 2023)
Cannabidiol (CBD) products gain increasing popularity amongst animal owners and veterinarians as an alternative remedy for treatment of stress, inflammation or pain in horses. Whilst the use of cannabinoids is banned in equine sports, there is limited information available concerning CBD detection times in blood or urine. The aim of this study was to determine the pharmacokinetic properties of CBD following oral administration in the horse to assist doping control laboratories with interpreting CBD analytical results. Part 1 (dose escalation study): Single oral administration of three escalating doses of CBD paste (0.2 mg/kg, n = 3 horses; 1 mg/kg, n = 3; 3 mg/kg, n = 5) with > 7 days wash-out periods in between. Part 2 (multiple dose study): oral administration of CBD paste (3 mg/kg, n = 6) twice daily for fifteen days. Multiple blood and urine samples were collected daily throughout both studies. Following study part 2, blood and urine samples were collected for two weeks to observe the elimination phase. Concentrations of CBD, its metabolites and further cannabinoids were evaluated using gaschromatography/tandem-mass-spectrometry. Pharmacokinetic parameters were assessed via two approaches: population pharmacokinetic analysis using a nonlinear mixed-effects model and noncompartmental analysis. AUC0-12 h and Cmax were tested for dose proportionality. During the elimination phase, the CBD steady-state urine to serum concentration ratio (Rss) was calculated. Oral CBD medication was well-tolerated in horses. Based on population pharmacokinetics, a 3compartment model with zero-order absorption most accurately described the pharmacokinetic properties of CBD. High volumes of distribution into peripheral compartments and high concentrations of 7-carboxy-CBD were observed in serum. Non-compartmental analysis identified a Cmax of 12.17 ± 2.08 ng/mL after single administration of CBD (dose: 3 mg/kg). AUC0-12 h showed dose proportionality, increase for Cmax leveled off at higher doses. Following multiple doses, the CBD terminal half-life was 161.29 ± 43.65 h in serum. Rss was 4.45 ± 1.04. CBD is extensively metabolized and shows high volumes of tissue distribution with a resulting extended elimination phase. Further investigation of the potential calming and anti-inflammatory effects of CBD are required to determine cut-off values for medication control using the calculated Rss.